Bilirubin Decreases Macrophage Cholesterol Efflux and ATP‐Binding Cassette Transporter A1 Protein Expression. Issue 5 (May 2017) - Wang, Dongdong; Tosevska, Anela; Heiß, Elke H.; Ladurner, Angela; Mölzer, Christine; Wallner, Marlies; Bulmer, Andrew; Wagner, Karl‐Heinz; Dirsch, Verena M.; Atanasov, Atanas G.
Abstract : Background: Mild but chronically elevated circulating unconjugated bilirubin is associated with reduced total and low‐density lipoprotein cholesterol concentration, which is associated with reduced cardiovascular disease risk. We aimed to investigate whether unconjugated bilirubin influences macrophage cholesterol efflux, as a potential mechanism for the altered circulating lipoprotein concentrations observed in hyperbilirubinemic individuals. Methods and Results: Cholesterol efflux from THP‐1 macrophages was assessed using plasma obtained from normo‐ and hyperbilirubinemic (Gilbert syndrome) humans (n=60 per group) or (heterozygote/homozygote Gunn) rats (n=20 per group) as an acceptor. Hyperbilirubinemic plasma from patients with Gilbert syndrome and Gunn rats induced significantly reduced cholesterol efflux compared with normobilirubinemic plasma. Unconjugated bilirubin (3–17.1 μmol/L) exogenously added to plasma‐ or apolipoprotein A1–supplemented media also decreased macrophage cholesterol efflux in a concentration‐ and time‐dependent manner. We also showed reduced protein expression of the ATP‐binding cassette transporter A1 (ABCA1), a transmembrane cholesterol transporter involved in apolipoprotein A1–mediated cholesterol efflux, in THP‐1 macrophages treated with unconjugated bilirubin and in peripheral blood mononuclear cells obtained from hyperbilirubinemic individuals. Furthermore, we demonstrated that bilirubin accelerates the degradation rate of the ABCA1 protein in THP‐1 macrophages. Conclusions: Cholesterol efflux from THP‐1 macrophages is decreased in the presence of plasma obtained from humans and rats with mild hyperbilirubinemia. A direct effect of unconjugated bilirubin on cholesterol efflux was demonstrated and is associated with decreased ABCA1 protein expression. These data improve our knowledge concerning bilirubin's impact on cholesterol transport and represent an important advancement in our understanding of bilirubin's role in cardiovascular disease.